The Depressed Female Characters From Their Intimidated Surrounding as Seen in The Yellow Wallpaper By Charlotte Perkin Gilman’s, A Rose For Emily By William Faulkner’s, and The Story of an Hour By Kate Chopin - Cut Ruby Miranda; Helmita Helmita (Jurnal Ilmiah Langue and Parole, 2019)
In writing this thesis, the writer discusses the depression of women because of patriarchal traditions, even though they already know about women's rights and freedoms. This patriarchal tradition is that men hold full power over anything and women must always obey the rules of men. The women are required not to do any activities, in terms of education and employment. Women are only allowed to do homework. This applies to all women, both single and married. This began in the 90s, especially in the United States. In writing the thesis, the writer uses psychological and feminist theories according to Sigmund Freud and Maggie Humm, who will explore the psychological side of women who are oppressed by the existence of this patriarchal custom. The purposes of this paper are: (1) To describe psychological-feminist cases in female characters (2) To analyze psychological-feminists in depressed female characters (3) To explain the psychological-feminist influence with female characters in the short story of The Yellow Wallpaper from Charlotte Perkins Gilman, A Rose For Emily from William Faulkner, The Story Of An Hour by Kate Chopin. The author uses descriptive qualitative methods in processing data. Through analysis of several existing sources and data. Based on available data, the writer discover how the psychology of depressed female characters from their environment is intimidated based on the short story. In fact women can become depressed because their freedom of expression is hampered and prohibited by tradition. With the writing of this thesis, it is hoped that the public can find out what exactly the meaning of women's emancipation is without having to put down women or men.